Characterization of Quantum Grade Interconnects. Issue 1 (1st December 2022) - Ferguson, R; Hall, S.R.G; Smith, J; Pitwon, R; Lee, B
Abstract: Quantum grade interconnects, which includes quantum grade optical fibre links and Quantum Photonic Integrated Circuits (QPICs), are rapidly developing components central to the successful development of the Quantum Internet and Quantum Key Distribution (QKD). These interconnects will present new metrological challenges that need to be addressed to ensure key support of future scientific and industrial development. Potential metrological solutions evolving alongside associated standardisation will ensure success and reliability of this advanced technology and provide key support to future scientific research and industrial manufacturing.